Remodelando tradições: os processos criativos e os significados do trabalho artesenal entre as louceiras do Córrego de Areia - Mendes, Francisca Raimunda Nogueira (2004)
This work investigates the handicraft practice of earthenware’s artisans at Corrego de Areia, a community located seven kilometers from the county of Limoeiro do Norte in the State of Ceara. The women engaged in this activity use clay as raw material which is changed into not only earthenware and sold at the region’s markets by the edges of Jaguaribe River but also decorative pieces which are sold at the Handicraft Center (Ceart) an institution kept by the State government and which has its headquarters in Fortaleza. Those objects present some characteristics that are similar to those found at other artisan centers in the State. It should be pointed that the artisans do not use lathes or other devices that they could resort to in order to increase production. Besides, the earthenware is not painted but naturally rendered in a strong red hue. Although marked by a utilitarian origin, this craftsmanship is produced today mostly for decorative purpose. In spite of this new approach, the principles that rule the art have not changed, that is, the manufacturing techniques, the earthenware baking and the tools used give expression to a creative tradition whose origin is far behind in time. The problems that are seen today are related to the intervention by the afore-mentioned institution, Ceart, which in the beginning of the 1990s started ordering pieces that should be fashioned according to designs presented to the artisans. The artisans’ creative work has thus been impaired because only trading interests are considered. Production of pieces is not, on the other hand, an activity to be regarded by its commercial value only. People involved in art develop concepts about the self and are lifted to artistic status due to their insertion into a unique cultural and symbolic context. Earthenware production includes wisdom, craftsmanship and investigation of world meaning, a knowledge that is passed along from one generation to another. The ideas developed in this fashion by those families give way to their daily lives, their common set of images and their art. While modeling their objects, the earthenware’s artisans model their own lives in an unending process that recreates and reshapes their cultural world.